2006
DOI: 10.1292/jvms.68.165
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Epidemiologic Genotyping of Staphylococcus aureus Isolates from Bovine Mastitic Milk in Hokkaido, Japan

Abstract: ABSTRACT. Two hundred thirty one Staphylococcus aureus isolates from bovine mastitic milk were discriminated into 60 patterns and 16 lineages by pulsed-field gel electrophoresis (PFGE). The tested isolates were also investigated using coagulase and capsule serotyping and PCR for possession of genes that encode staphylococcal enterotoxins (sea to sei), enterotoxin-like toxins (selj to selr), and toxic shock syndrome toxin (tst). One hundred seventy three of the isolates (74.9%) possessed one or more toxin genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 28 publications
3
31
1
Order By: Relevance
“…Though the 88 S. aureus isolated between 2010 and 2012 belong to 14 different pulsotypes, 3 of them (A, B, D) group together 72 % and 5 of them (A, B, D, N, Z), 83 % of the isolates, confirming, like in other studies, that a restricted number of S. aureus clones are present within a herd or a farm (Hata et al 2006;Aires-de-Sousa et al 2007;Rabello et al 2007;Anderson et al 2012). Nevertheless, apart from the A and B pulsotypes (>90 % similarity), the other pulsotypes are not closely related and represent distinct lineages (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…Though the 88 S. aureus isolated between 2010 and 2012 belong to 14 different pulsotypes, 3 of them (A, B, D) group together 72 % and 5 of them (A, B, D, N, Z), 83 % of the isolates, confirming, like in other studies, that a restricted number of S. aureus clones are present within a herd or a farm (Hata et al 2006;Aires-de-Sousa et al 2007;Rabello et al 2007;Anderson et al 2012). Nevertheless, apart from the A and B pulsotypes (>90 % similarity), the other pulsotypes are not closely related and represent distinct lineages (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…1 and Table 2). The majority of seg and sei distribution studies show that these genes are always detected together in S. aureus because they coexist on a common genetic element, a so-called enterotoxin gene cluster (Jarraud et al, 2001;Rosec and Gigaud, 2002;Stephan et al, 2002;Scherrer et al, 2004;Katsuda et al, 2005;Bania et al, 2006;Boerema et al, 2006;Hata et al, 2006;Kérouanton et al, 2007). It should also be noted that none of our isolates possessed the see, seh, sej, or tst genes, and on 15 out of 20 farms tested, no enterotoxigenic staphylococci were recovered from either mastitic quarter milk or bulk tank milk (Table 2).…”
Section: Pcr Amplification Of Genes Encoding Staphylococcal Enterotoxinsmentioning
confidence: 99%
“…Traditionally, five classical antigenic SE types (SEA, SEB, SEC, SED, and SEE) were recognized. However, in recent years, the existence of new types of SEs, including enterotoxin-like (SEl) toxins (SEG, SEH, SEI, SElJ, SElK, SElL, SElM, SElN, SElO, SElP, SElQ, SElR, SElU, SElU2, and SElV) has been reported and their genes described (Letertre et al, 2003;Lina et al, 2004;Omoe et al, 2004;Jørgensen et al, 2005a;Bania et al, 2006;Boerema et al, 2006;Hata et al, 2006;Thomas et al, 2006). A distantly related protein, toxic shock syndrome toxin 1 (TSST-1), also produced by S. aureus, was the first toxin shown to be involved in the toxic shock syndrome of humans and animals (Akineden et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A limited number of molecular studies have been published that explored the population structure and genetic relationships of S. aureus causing bovine mastitis (de Sousa et al, 2007;Hata et al, 2006;Jørgensen et al, 2005;Katsuda et al, 2005;Reinoso et al, 2008). The results of our recent study demonstrated that a Multiple Locus Variable Number Tandem Repeats (VNTR) Analysis (MLVA) could be used as a fast, inexpensive, highly discriminatory, reproducible, stable and portable typing method for epidemiological tracing of human S. aureus (Ikawaty et al, 2008).…”
Section: Introductionmentioning
confidence: 95%